Proceedings of the 7th International Conference on English Language and Teaching (ICOELT 2019) 2020
DOI: 10.2991/assehr.k.200306.002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Use of Drawing Task to Enhance Students’ Reading Comprehension

Abstract: This study explores the use of drawing task in the implementation of task-based language teaching to teach reading comprehension. The result reported here is a part of an experimental study which sought to look at the contribution of different task types on the students' reading comprehension. One of the tasks was drawing task. This study involved one randomly selected class of the 10th year senior high school students in Padang (West Sumatera). The data were collected through reading test and observation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In relation to TBLT, experimental studies have found that the use of TBLT increases EFL students' intrinsic motivation (NamazianDost et al, 2017;Pietri, 2015). In a similar vein, in Indonesian context, Sukma et al (2020) and Saputro et al (2021) found that TBLT enhanced the students' motivation and enthusiasm to learn English through meaningful tasks. The Indonesian students enjoyed TBLT classroom learning activities and got engaged with it (Saputro et al, 2021).…”
Section: Tblt Generates Students' Intrinsic Motivationmentioning
confidence: 84%
See 4 more Smart Citations
“…In relation to TBLT, experimental studies have found that the use of TBLT increases EFL students' intrinsic motivation (NamazianDost et al, 2017;Pietri, 2015). In a similar vein, in Indonesian context, Sukma et al (2020) and Saputro et al (2021) found that TBLT enhanced the students' motivation and enthusiasm to learn English through meaningful tasks. The Indonesian students enjoyed TBLT classroom learning activities and got engaged with it (Saputro et al, 2021).…”
Section: Tblt Generates Students' Intrinsic Motivationmentioning
confidence: 84%
“…The key distinctive aspect of TBLT lies in the provision of tasks as the main classroom activities (Ellis, 2009;Sukma et al, 2020). Advocates of TBLT have conceptualised tasks in different ways.…”
Section: Defining Task-based Language Teaching (Tblt)mentioning
confidence: 99%
See 3 more Smart Citations